Medical robotics : minimally invasive surgery - Gomes, Paula (M. Paula S. F.) (Cambridge : Woodhead Publishing, 2012)
"Advances in research have led to the use of robotics in a range of surgical applications. Medical robotics: Minimally invasive surgery provides authoritative coverage of the core principles, applications and future potential of this enabling technology. Beginning with an introduction to robot-assisted minimally invasive surgery (MIS), the core technologies of the field are discussed, including localization and tracking technologies for medical robotics. Key applications of robotics in laparoscopy, neurology, cardiovascular interventions, urology and orthopaedics are considered, as well as applications for ear, nose and throat (ENT) surgery, vitreoretinal surgery and natural orifice transluminal endoscopic surgery (NOTES). Microscale mobile robots for the circulatory system and mesoscale robots for the gastrointestinal tract are investigated, as is MRI-based navigation for in vivo magnetic microrobots. Finally, the book concludes with a discussion of ethical issues related to the use of robotics in surgery. With its distinguished editor and international team of expert contributors, Medical robotics: Minimally invasive surgery is a comprehensive guide for all those working in the research, design, development and application of medical robotics for surgery. It also provides an authoritative introduction for academics and medical practitioners working in this field. Provides authoritative coverage of the core principles, applications and future potential of medical robotics. Introduces robot-assisted minimally invasive surgery (MIS), including the core technologies of the field and localization and tracking technologies for medical robotics. Considers key applications of robotics in laparoscopy, neurology, cardiovascular interventions, urology and orthopaedics."--Publisher's description.
1. Introduction to robot-assisted minimally invasive surgery (MIS) / V. Vitiello, K.-W. Kwok and G.-Z. Yang -- 2. Localization and tracking technologies for medical robotics / N. Glossop -- 3. Robotics for neurosurgery / T.L. Cossetto, K. Zareinia, and G.R. Sutherland -- 4. Robotic systems for cardiovascular interventions / M.A. Zenati and M. Mahvash -- 5. Robotics in orthopaedic surgery / A. Hodgson -- 6. Robotic-assisted knee replacement surgery / C. Plaskos, J.A. Koenig and C.E. Ponder -- 7. Robotics in ear, nose and throat (ENT) surgery / B. Bell, M.D. Caversaccio and S. Weber -- 8. Robot-assisted vitreoretinal surgery / H.C.M. Meenink, R. Hendrix, G.J.L. Naus, M.J. Beelen, H. Nijmeijer and M. Steinbuch, E.J.G.M. van Oosterhout and M.D. de Smet -- 9. Robotics for minimally invasive surgery (MIS) and natural orifice transluminal endoscopic surgery (NOTES) / J. Reynoso, A. Meyer, J. Unnirevi and D. Oleynikov -- 10. Mesoscale mobile robots for gastrointestinal minimally invasive surgery (MIS) / J.L. Gorlewicz, R.J. Webster III and P. Valdastri -- 11. Real-time software platform using MRI for in vivo navigation of magnetic microrobots / K. Belharet, D. Folio and A. Ferreira -- 12. Robotic surgery and ethical challenges / N. Sharkey and A. Sharkey.
Includes bibliographical references and index.
Keywords: Robotics in medicine; Artificial intelligence -- Medical applications; Endoscopic surgery; Laparoscopic surgery; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Robotics in medicine; Artificial intelligence -- Medical applications; Endoscopic surgery; Laparoscopic surgery; Minimally Invasive Surgical Procedures; Robotics